The Effect of Foliar Fertilizers as Substitution Media on The Growth of Chrysanthemum morifolium Shoot by In Vitro Culture - Handayani, Etty (Tropical Plantation Journal, 2025)
The production of chrysanthemum plants in large quantities can be obtained by in vitro growth of chrysanthemums. The growth media that is often used is MS media which has a relatively high price. Therefore, a substitution medium that has a relatively affordable price is needed in the form of foliar fertilizer media with coconut water and ambon bananas added. This study aims to examine the best medium that can be used for in vitro chrysanthemum growth. The research was carried out in June-September 2020 at the In Vitro Culture Laboratory, Faculty of Agriculture, University of Muhammadiyah Yogyakarta. The research was carried out by a single-factor experimental method with 7 treatments and each had 5 replicates and each replicate consisted of 3 samples arranged with a Complete Random Design (RAL). The treatment that was experimented with was the use of foliar fertilizers in the form of Growmore and Hyponex Green with the addition of coconut water and bananas. The concentrations of Growmore foliar fertilizer given were 3 g/l, 4 g/l, and 5 g/l. The concentrations of Green Hyponex foliar fertilizer given were 3 g/l, 4 g/l, and 5 g/l. The results of the research showed that foliar fertilizer added with coconut water and banana ambon could be used as a substitution medium for MS media in chrysanthemum growth in vitro. The use of Growmore 4 g/l foliar fertilizer shows the best hail against the tall growth of chrysanthemum shoots in vitro